The Industry of Creative Leisure in the Urban Space of the Metropolis - MEDVED, Eleonora I.; KISELEVA, Olga I.; LEVINA, Irina D.; KAYTANDZHYAN, Mariia G.; GRIBKOVA, Galina I. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
The relevance of the study is due to the fact that today, in the conditions of the creative leisure industry, the demands on the organization of free time of residents of the metropolitan metropolis are increasing. Employees of cultural institutions should possess modern technologies for organizing leisure activities of various categories of the population and attract attention to themselves, focusing exclusively on high-quality and relevant leisure forms. This article aims to analyze the main parameters of the industry of creative leisure in the urban space of Moscow. Leading approach to the study of this problem is the descriptive method. The materials of the paper imply the practical significance for the university teachers of the economical specializations.